KAPITALISASI LEMBAGA PENDIDIKAN ISLAM - M. Yunus; Dian Dwi Alifatul Faizah (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2023)
The problems of Islamic education that are developing in schools today are numerous, one of which is capitalism Islamic education, education that the rights of each individual person are limited by financial ability. That is the high cost of private education, which in fact is an Islamic educational institution that usually has the word Islam behind the name of the school, such as Islamic elementary school, Islamic junior high school and the like. make education has come out of its true purpose. The paradigm of Islamic education does not distinguish between social groups in society, because learning is the right of every individual, everyone has the right to get a school education. It is time for us to implement the "social justice" paradigm, using the "human empowerment approach". approach to placing humans as humans. Humans are not adapted to goods. Humans are independent-autonomous beings, have potential that can be developed and realized. So it's fair that education will be implemented if we are all serious about transforming education with the concept of "humanizing humans".